Characterizing fluorescent dissolved organic matter in a membrane bioreactor via excitation–emission matrix combined with parallel factor analysis. (June 2016) - Maqbool, Tahir; Quang, Viet Ly; Cho, Jinwoo; Hur, Jin
Graphical abstract: Highlights: EEM–PARAFAC was successfully applied to track fluorescent DOM in MBRs. Tryptophan-like component can be used as the surrogate of EPS production in sludge. Tyrosine-like component is closely related to the stability of sludge. Tryptophan-like component is transformed to microbial humic-like component. Protein-like components are mostly responsible for membrane fouling in MBRs. Abstract: In this study, we successfully tracked the dynamic changes in different constitutes of bound extracellular polymeric substances (bEPS), soluble microbial products (SMP), and permeate during the operation of bench scale membrane bioreactors (MBRs) via fluorescence excitation–emission matrix (EEM) combined with parallel factor analysis (PARAFAC). Three fluorescent groups were identified, including two protein-like (tryptophan-like C1 and tyrosine-like C2) and one microbial humic-like components (C3). In bEPS, protein-like components were consistently more dominant than C3 during the MBR operation, while their relative abundance in SMP depended on aeration intensities. C1 of bEPS exhibited a linear correlation ( R 2  = 0.738; p  < 0.01) with bEPS amounts in sludge, and C2 was closely related to the stability of sludge. The protein-like components were more greatly responsible for membrane fouling. Our study suggests that EEM–PARAFAC can be a promising monitoring tool to provide further insight into process evaluation and membrane fouling during MBR operation.